Infrared Spectra of Deprotonated Dicarboxylic Acids: IRMPD Spectroscopy and Empirical Valence‐Bond Modeling. Issue 6 (27th February 2019) - Thaunay, Florian; Calvo, Florent; Nicol, Edith; Ohanessian, Gilles; Clavaguéra, Carine
Abstract: Experimental infrared multiple‐photon dissociation (IRMPD) spectra recorded for a series of deprotonated dicarboxylic acids, HO2 (CH2 ) n CO 2 - ( n =2–4), are interpreted using a variety of computational methods. The broad bands centered near 1600 cm −1 can be reproduced neither by static vibrational calculations based on quantum chemistry nor by a dynamical description of individual structures using the many‐body polarizable AMOEBA force field, strongly suggesting that these molecules experience dynamical proton sharing between the two carboxylic ends. To confirm this assumption, AMOEBA was combined with a two‐state empirical valence‐bond (EVB) model to allow for proton transfer in classical molecular dynamics simulations. Upon suitable parametrization based on ab initio reference data, the EVB‐AMOEBA model satisfactorily reproduces the experimental infrared spectra, and the finite temperature dynamics reveals a significant amount of proton sharing in such systems. Abstract : Proton dynamics : Experimental infrared multiple photon dissociation (IRMPD) spectra are recorded for a series of deprotonated dicarboxylic acids and interpreted with an empirical valence‐bond model associated to the AMOEBA polarizable force field.